From the Classic Novel to the Crime Novel: A Genre Paradigm Shift in Artistic Reception - Fedunina, Olga (Slavica, 2023)
The article deals with the cases of classical works completion, in which their genre nature undergoes a change. The texts are transferred from the sphere of high literature to the low one, as the continuing of the plot with the criminal line becomes the main method. The material for the analysis is “The very same Tatiana” by A. and S. Litvinovs, as well as the novel “Death Comes to Pemberley” by P.D. James. I show that one of the most relevant genres in this change of genre paradigm is “by victim investigation”, which allows to retain some recognizable items of the classic primary source.